'Serving the turn': collaboration and proof in illegal hand-press period books - Grace Egan; Colin Johnston (Ilha do Desterro)
This article considers the proofing of illegally-printed texts, primarily during the sixteenth and seventeenth centuries.  We argue that proofing – the practice of correcting a text during the printing process – is key to understanding the social dynamics of authorship, and the strains on production resulting from political suppression of the press during this period.  We look at the evidence of proofing left in books (usually religious pamphlets), as well as the testimony of authors and printers.  These sources reveal that illegal printing necessitated a remarkable degree of team work.